Arguments for the abolition of the defence of mental impairment. Issue 1 (2nd January 2023) - Darjee, Rajan; Marsh, Tim
Abstract : This article summarises arguments for abolishing the mental impairment defence, using the example of the defence in Victoria, taking a historical and comparative approach. It considers the defence in practice, its origins and stagnation in medieval and Victorian England, a better approach based on modern developments in the UK and Europe, its resistance to meaningful reform, and its failure to achieve its laudable, humane and principled aim of sparing vulnerable people with severe mental health problems from punishment. We conclude that the only way to actually achieve this aim is to abolish the mental impairment defence and replace it with an approach that allows for flexible mental health disposals for mentally disordered offenders based on clinical needs and, where necessary, the need for containment, incorporated in and aligned with mental health legislation, regardless of culpability, and with modern systems and services that bring Victoria out of the nineteenth century.